Femininity and Masculinity in Arabic Words: Gender Marking in Muslim Cosmology - Muassomah Muassomah; Wildana Wargadinata; Galuh Nur Rohmah; Rohmani Nur Indah; Siti Masitoh; Istiadah Istiadah; Irwan Abdullah (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
The Modern Standard Arabic (MSA) language strongly indicates the sociolinguistic phenomenon as it reflects gender marking in language use. This study aims to explore how the Arabic letters attributed to specific gender identities, how the gender ideology of Arab culture create gender biases, and how the biases influence Arab social structure. It uses aspects of masculinity and femininity of Arabic letters that affect gender inequality and order of values on language, tradition and culture. Masculine letters are letters that have the property of being able to hold and entail other letters, while feminine letters that have the nature can be attached with other letters but cannot be attached. In this study, Arabic letters were mapped by observing their use in written and oral interaction in the contexts of Arab as first and second language. This research is a qualitative in nature. The data on ideology's influence on social structure were collected through interviews with three key informants representing their areas of expertise on language anthropology, sociolinguistic, and applied linguistic. The morphological analysis was carried out to identify the internal structure of the words. The sociolinguistic analysis explored the linguistic construction that to social construction. The finding showed that their internal structures, these letters were classified as masculine or feminine. From the sociolinguistic point of view, gender issues following social construction that has already formed gender relations. In other words, Arabic letters affect the order of values that tend to be gender-biased in the Arabic context.